158 The effect of sire fecal egg count estimated breeding value on antibody production of grazing Katahdin lambs. (28th November 2020) - Bentley, Kelsey; Weaver, Andrew R; Burke, Joan M; Morgan, Jim; Wright, Lee; Greiner, Scott P; Bowdridge, Scott A
Abstract: Over the past two years of mating high (Hi) or low (Lo) fecal egg count (FEC) EBV Katahdin rams randomly mated to Katahdin ewes, reduced FEC in lambs has been the hallmark trait observable at weaning. Upon additional analysis, death loss in lambs also segregated with sire FEC EBV; whereas, HiFEC-sired lambs had a death loss of 29.9% in 2018 and 14.5% in 2019. Yet, LoFEC-sired lambs had a death loss of 10% in both years. Increased death loss in 2018 may have been due to an outbreak of Clostridium perfringens Type-A and as a result lambs in 2019 were vaccinated for Clostridium type A. Regardless, this had no impact on death loss in LoFEC-sired lambs. Therefore, it can be hypothesized that sire FEC EBV indirectly selects for enhanced, generalized immunity. To initially test this hypothesis, serum was collected from HiFEC- and LoFEC-sired lambs weekly, prior to and after typical clostridium toxoid vaccination and boostering. Lamb serum was pooled by week and within sire, where there were 4 sires per FEC EBV group. Serum was analyzed for total immunoglobulin-G (IgG) by using absorbance at 450nm as the metric. Data were analyzed by using the general linear model of SAS with fixed effects of sire EBV type and week. A comparison of means was conducted by using the LS means procedure with Bonferroni adjustment. Absorbance of serum from LoFEC-sired lambs was higher across all time points than that of serum from HiFEC-sired lambs (1.66 vs. 1.41 ± 0.04; P < 0.0001), meaning that LoFEC-sired lambs had higher circulating IgG than lambs sired by HiFEC rams. Taken together, these data provide preliminary evidence that indicate segregation of lamb generalized immunity by sire FEC EBV.